Mechanical behaviour of micro-capsules and their rupture under compression - Ghaemi, Ali; Philipp, Alexandra; Bauer, Andreas; Last, Klaus; Fery, Andreas; Gekle, Stephan (Chemical Engineering Science, 2016)
Understanding the deformation of micro-capsules (MCs) and especially the mechanism of their rupture is of crucial importance for their performance in various applications. Mechanical instability can on the one hand be a failure mechanism, resulting in undesired release, but can on the other hand be used as a release trigger. In this work, finite element analysis together with nano-indentation experiments is applied to characterize the deformation of single filled MCs made of melamin-formaldehyde. The simulations reveal that the capsules undergo different deformation regimes: starting from linear elastic deformation, upon further compression the MCs yield and are plastically deformed. The final step is a strain hardening regime, where the maximum stress rapidly increases till the MCs rupture. Finally, we describe the MCs rupture mechanism obtained from numerical simulation and experimental results. We show that the axial and radial stresses cause significant thinning of the shell at the MC's equator, and that the circumferential stress leads to rupture along the meridians of the MC.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Finite element analysis; Microcapsule; Nanoindentation; Plasticity; Rupture; Simulations